Accurate and efficient non-invasive strategy for early identification of chronic thromboembolic pulmonary hypertension after acute pulmonary embolism (InShape II study). (25th November 2020) - Klok, E; Boon, G.J.A.M; Ende-Verhaar, Y.M; Bavalia, R; Delcroix, M; Dzikowska-Diduch, O; Kurnicka, K; Mairuhu, A.T.A; Middeldorp, S; Pruszczyk, P; Ruigrol, D; Verhamme, P; et al.
Abstract: Background: The current diagnostic delay of chronic thromboembolic pulmonary hypertension (CTEPH) after acute pulmonary embolism (PE) is unacceptably long exceeding 1 year, causing loss of quality-adjusted life years and excess mortality. Validated screening strategies to diagnose CTEPH earlier are lacking. Importantly, performing echocardiography in all PE patients for this purpose has a low diagnostic yield, is associated with overdiagnosis and is not cost-effective. Moreover, expertise in performing high-quality PH-dedicated echocardiograms may not be available outside expert centers. Aim: To validate a simple screening strategy aimed at identifying CTEPH early in the course after acute PE, avoiding echocardiography if possible (Figure 1). Methods: In this prospective, international, multicenter management study, consecutive PE survivors were managed according to the predefined algorithm starting three months after acute PE. All were followed for a total period of two years. The study protocol was approved by all local IRBs and all patients provided informed consent. Results: 424 patients were included across three European countries (Table 1). Following the algorithm, CTEPH was considered excluded in 343 (81%) patients based on clinical pre-test probability assessment by the "CTEPH prediction score", evaluation of symptoms and application of the "CTEPH rule-out criteria" (Figure 1); only 19% was subjected to echocardiography. Only 1 of 343 patients managed without echocardiography was diagnosed with CTEPH, 10 months after initial PE, for a failure rate of 0.29% (95% CI 0–1.6%). Overall, 13 patients were diagnosed with CTEPH (incidence 3.1%), of whom 10 within 4 months after PE diagnosis. Conclusions: The algorithm accurately ruled out CTEPH and avoided echocardiography in 81% of patients. The vast majority of CTEPH cases were identified early in the course of acute PE which is a considerable improvement compared to current clinical practice with an economic use of healthcare resources. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): This study was supported by unrestricted grants from Bayer/Merck Sharp & Dohme (MSD) and Actelion Pharmaceuticals Ltd. F.A. Klok and G.J.A.M. Boon were supported by the Dutch Heart Foundation (2017T064).